Effects of dietary calcium formate and malic acid on nursery pig growth performance - R O Gottlob; J M Benz; C N Groesbeck; R C Sulabo; Michael D Tokach; Jim L Nelssen; Robert D Goodband; Joel M DeRouchey; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2006)
A total of 180 weanling pigs (initially 14.1 lb and 18 ± 3 d of age, PIC) were used to determine the effects of dietary calcium formate or malic acid on nursery pig growth performance. Treatments were arranged in a 2 × 3 factorial, with or without an antimicrobial, and with or without calcium formate or malic acid, for a total of six dietary treatments: 1) negative control (no organic acids or antimicrobials); 2) positive control (feed containing 140 g/ton neomycin sulfate, 140 g/ton oxytetracycline; neo/oxy); 3) negative control feed containing malic acid; 4) positive control feed containing malic acid; 5) negative control feed containing calcium formate; 6) positive control feed containing calcium formate. There were no interactions (P>0.10) between the antimicrobial and the organic acids. Overall, pigs fed diets containing neo/oxy had greater ADG and ADFI (P<0.04) than did pigs fed diets without an antimicrobial. There were no differences in growth performance between pigs fed the control diet and pigs fed diets containing organic acids. These data suggest that neo/oxy increases ADG and ADFI of weanling pigs. Neither malic acid nor calcium formate are suitable replacements for neo/oxy for growth performance in nursery pigs.; Swine Day, 2006, Kansas State University, Manhattan, KS, 2006
Keywords: Kansas Agricultural Experiment Station contribution; no. 08-83-S; Swine day; 2006; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 966; Nursery pig; Antibiotics; Organic acids; Water; Growth; Swine